Radio-frequency integrated-circuit engineering - Nguyen, Cam (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
'Complementary metal-oxide-semiconductor (CMOS) is a technology for constructing integrated circuits. This book thoroughly discusses the theory, analysis, design, and high-frequency/high-speed characteristics and applications of printed-circuit transmission lines used in integrated circuits and systems. It discusses applications in all areas of high-frequency technology, including wireless communications, optical engineering, and computers. Accompanied by a solutions manual, this text is ideal for senior and advanced undergraduate students, as well as RF microwave engineers, optical engineers, solid-state device engineers, and computer engineers'--
Includes bibliographical references and index.
Keywords: Radio frequency integrated circuits